Dinamika motivasi berprestasi mahasiswa baru dalam adaptasi cabang bela diri: sebuah kajian psikologi olahraga - Musthofa, Nur Hidayatul (Maliki Interdisciplinary Journal, 2026)
This article discusses how achievement motivation develops in new students adjusting to a different martial art from their previous discipline. This study was compiled through a literature review analyzing various national and international journals, as well as publications by lecturers at UIN Maulana Malik Ibrahim Malang. The discussion focuses on the role of achievement motivation, self-efficacy, social support, and engagement in the student adaptation process. An applied approach is used to link sports psychology theory to the experiences of students transitioning from karate to pencak silat. The study results indicate that mental readiness and the ability to adapt to new techniques are strongly associated with achievement motivation. Both form an important foundation for new students’ performance. These findings imply the need for active roles by coaches, educational institutions, and students in creating a more supportive and effective sports development process.